INTERNALISASI NILAI-NILAI TOLERANSI MELALUI KEGIATAN MA’HAD DI PONDOK PESANTREN TARBIYATUL MU’ALLIMIEN AL-ISLAMIYAH AL-AMIEN PRENDUAN - Muru'atul Afifah; Hikma Nurfadila (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
The process of internalizing the values ​​of tolerance through Ma'had activities at the Al-Amien Prenduan Islamic Boarding School has been implemented, this can be seen from the condition of the students who mingle even though they come from different regional and ethnic backgrounds both from within and outside the country and from different backgrounds. different groups such as NU, Muhammadiyah or even Manhaj Salafi with their habit of wearing the veil in the daily lives of female students The problem raised in this study is how the process of internalizing tolerance values ​​through Ma'had activities. Second, what are the supporting and inhibiting factors in the process of internalizing tolerance values ​​through Ma'had activities at the TMI Al-Amien Prenduan Islamic Boarding School. In this study using a descriptive qualitative approach. The method used is the method of interviews, observation and documentation. For data analysis, researchers used the Miles and Hubberman models through data collection, data reduction, data presentation and drawing conclusions. From the validity of the data, researchers used triangulation with source triangulation. The results of research on the process of internalizing tolerance values ​​through Ma'had activities at the pondok are through: Lecture Activities, Santri Daily Activities, Santri Organizational Activities, and Year End Peak Activities. The factors that support the process of internalizing tolerance values ​​through Ma's activities 'had namely: Educators and Traditions in carrying out the sunnah of Pondok. While the inhibiting factors are: individualism, fanaticism and character.